2014
DOI: 10.1074/jbc.m114.564120
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Hyaluronan Production Promotes Acquisition of Cancer Stem Cell Signatures through the Coordinated Regulation of Twist and the Transforming Growth Factor β (TGF-β)-Snail Signaling Axis

Abstract: Background: Hyaluronan overproduction is implicated in breast cancer progression. Results: Hyaluronan overproduction expands cancer stem-like cells through the up-regulation of Snail and Twist expression. Conclusion: Hyaluronan overproduction allows plastic cancer cells to revert to stem cell states via Twist and the transforming growth factor ␤-Snail signaling axis. Significance: These findings will help to understand the unique hyaluronan-dependent mechanisms that govern cancer cell plasticity and cancer ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
79
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 41 publications
6
79
0
Order By: Relevance
“…HAS2 overexpression not only induces the EMT processes, but also provides additional stimulus driving the conversion to cancer stem cells (CSC) phenotype. Induction of HAS2 expression in HAS2 +Neo cells from transgenic mice resulted in frequent occurrence of CD44hi/CD24lo population 23. Our findings were in concordance with the observed functional effects of HAS2 in EMT and CSC in these studies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…HAS2 overexpression not only induces the EMT processes, but also provides additional stimulus driving the conversion to cancer stem cells (CSC) phenotype. Induction of HAS2 expression in HAS2 +Neo cells from transgenic mice resulted in frequent occurrence of CD44hi/CD24lo population 23. Our findings were in concordance with the observed functional effects of HAS2 in EMT and CSC in these studies.…”
Section: Discussionsupporting
confidence: 92%
“…However, recently, HAS2 has been described to promote EMT, independent of its enzymatic activity. HAS2 expression, independent of extracellular HA-CD44 interaction, was involved in EMT induction or the CSC conversion 7 23. In line with the observation, this study showed that the poor prognosis of HAS+AR− cancers was not dependent on CD44 expression.…”
Section: Discussionsupporting
confidence: 83%
“…Adding to the heterogeneity of cancer cells, signals from stromal cells and extracellular matrix (ECM) components can also promote and maintain cancer stem/stem-like cells (CSCs) (Lu et al 2012; Chanmee et al 2014; Chen et al 2014a; Whatcott et al 2015b). CSCs represent a population of cancer cells thought to be responsible for tumor initiation and progression (Magee et al 2012).…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…TGF-β-mediated EMT requires participation of HAS2 (Porsch et al, 2013). Overproduction of HA is needed to drive EMT via Twist and TGF-β–Snail signaling (Chanmee et al, 2014, 2016). TGF-β1 is growth-inhibitory to normal epithelial cells, whereas hyaluronidase PH-20 counteracts the effect of TGF-β1 (Chang, 1997), Chang (1998, 2002).…”
Section: Hyal-2 Is a Cognate Receptor For Tgf-β: Signaling Via Hyal-2mentioning
confidence: 99%